Antagonism of 5-HT2 receptors attenuates self-sustained firing of human motor units - Goodlich, Benjamin I.; Pearcey, Gregory E.P.; Del Vecchio, Alessandro; Horan, Sean A.; Kavanagh, Justin J. (The Journal of Physiology, 2024)
Abstract: 5-HT2 receptors on motoneurones play a critical role in facilitating persistent inward currents (PICs). Although facilitation of PICs can enhance self-sustained firing after periods of excitation, the relationship between 5-HT2 receptor activity and self-sustained firing in human motor units (MUs) has not been resolved. MU activity was assessed from the tibialis anterior of 10 healthy adults (24.9 ± 2.8 years) during two contraction protocols. Both protocols featured steady-state isometric contractions with constant descending drive to the motoneurone pool. However, one protocol also included an additional phase of superimposed descending drive. Adding and then removing descending drive in the middle of steady-state contractions altered MU firing behaviour across the motor pool, where newly recruited units in the superimposed phase were unable to switch off (P = 0.0002), and units recruited prior to additional descending drive reduced their discharge rates (P < 0.0001, difference in estimated marginal means (∆) = 2.24 pulses/s). The 5-HT2 receptor antagonist, cyproheptadine, was then administered to determine whether changes in MU firing were mediated by serotonergic mechanisms. 5-HT2 receptor antagonism caused reductions in MU discharge rate (P < 0.001, ∆ = 1.65 pulses/s), recruitment threshold (P = 0.00112, ∆ = 1.09% maximal voluntary contraction) and self-sustained firing duration (P < 0.0001, ∆ = 1.77s) after the additional descending drive was removed in the middle of the steady-state contraction. These findings indicate that serotonergic neuromodulation plays a key role in facilitating discharge and self-sustained firing of human motoneurones, where adaptive changes in MU recruitment must occur to meet the demands of the contraction. (Figure presented.). Key points: Animal and cellular preparations indicate that somato-dendritic 5-HT2 receptors regulate the intrinsic excitability of motoneurones. 5-HT2 receptor antagonism reduces estimates of persistent inward currents in motoneurones, which contribute to self-sustained firing when synaptic inputs are reduced or removed. This human study employed a contraction task that slowly increased (and then removed) the additional descending drive in the middle of a steady-state contraction where marked self-sustained firing occurred when the descending drive was removed. 5-HT2 receptor antagonism caused widespread reductions in motor unit (MU) discharge rates during contractions, which was accompanied by reduced recruitment threshold and attenuation of self-sustained firing duration after the removal of the additional descending drive to motoneurones. These findings support the role that serotonergic neuromodulation is a key facilitator of MU discharge and self-sustained firing of human motoneurones, where adaptative changes in MU recruitment must occur to meet the demands of the contraction.
CRIS-Team Scopus Importer:2024-04-05
Keywords: high-density electromyography; monoamine; motoneurone; neuromodulation; persistent inward current